Process of career identity formation among adolescents: components and factors. Issue 9 (September 2020) - Batool, Syeda Shahida; Ghayas, Saba
Abstract: To qualitatively explore the process and factors that influence career identity formation, data were collected from 18 middle adolescents of age ranged between 15 and 17 years. Thematic analysis revealed that the process of career identity comprised exploration, commitment, and reconsideration components. Eight factors (viz., parental influence, peer influence, religious orientation, media, nationalism, economic conditions, teachers' power, and personal preferences) appeared to influence the exploration component of career identity. Exploration of possible careers lead towards commitment after being influenced by expected outcomes (economic benefits, religious benefits, social standards, and functional gains). Satisfaction with the expected outcomes of the explored career help participants to reach at commitment. After being committed to any career, identity appeared to be bifurcated into identity achievement and identity confusion. The adolescents who were contented and consistent appeared to achieve their career identity and identity confusion lead towards the reconsideration of their career plans. Eventually, at one side, reconsideration may lead towards exploration with new choices and opportunities. While on the other hand, as a result of reassurance, individuals may revert back towards their previously committed career identity. This paper provides theoretical and practical implications for the career development of adolescents. Abstract : Psychology; Career; Identity formation; Process; Thematic analysis; Adolescence.